If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -7 = 5m Reorder the terms: -7 + 2m = 5m Solving -7 + 2m = 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. -7 + 2m + -5m = 5m + -5m Combine like terms: 2m + -5m = -3m -7 + -3m = 5m + -5m Combine like terms: 5m + -5m = 0 -7 + -3m = 0 Add '7' to each side of the equation. -7 + 7 + -3m = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -3m = 0 + 7 -3m = 0 + 7 Combine like terms: 0 + 7 = 7 -3m = 7 Divide each side by '-3'. m = -2.333333333 Simplifying m = -2.333333333
| 4x+7=7x+-3 | | E=1l+2.25h | | 17=7w-4 | | 49=7(n+6) | | 9x+3=3x-4 | | 4688x+787878y=0 | | 2x^20-8x^10+x-2=0 | | 4(-12k-6)=8(-k+2) | | 2(5x+3)=4x+10+6x-4 | | (9x-40)=(5x+8) | | 6x-5=-3x+13 | | x+x+10=550 | | 65x+50y=63 | | 3x^2(x-3)+7x(x-3)-20(x-3)=0 | | p=300-2w-2l | | -7x+3=10 | | -8=33-5q | | 10x^2=14-8x | | 3/5x-x/4=-2 | | 6w-w=40 | | 4x-11=-5(-7x-4) | | 6/4(x-3) | | 6+(52-5)2=p | | (9x-40)= | | 17-13*6*x= | | 5b^2+6=851 | | 27x-5=9x+5 | | y=5x-10is | | 36m^2-25=0 | | 5a-2=5a-2 | | 18=m+n | | b^2+7=33 |